2021
DOI: 10.1111/nph.17192
|View full text |Cite
|
Sign up to set email alerts
|

Plastidial retrograde modulation of light and hormonal signaling: an odyssey

Abstract: The transition from an engulfed autonomous unicellular photosynthetic bacterium to a semiautonomous endosymbiont plastid was accompanied by the transfer of genetic material from the endosymbiont to the nuclear genome of the host, followed by the establishment of plastid-to-nucleus (retrograde) signaling. The retrograde coordinated activities of the two subcellular genomes ensure chloroplast biogenesis and function as the photosynthetic hub and sensing and signaling center that tailors growth-regulating and ada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 45 publications
0
29
0
Order By: Relevance
“…Technology to detect and track retrograde signaling pathways from plastids to nuclei in response to, for example, singlet O 2 , protein folding stress, redox and metabolites. These retrograde pathways involve a range of small molecules and likely also protein signaling cascades ( Jiang and Dehesh, 2021 ; Muñoz and Munné-Bosch, 2020 ; Pesaresi and Kim, 2019 ). Non-invasive, high-resolution and high-sensitivity imaging technologies should be developed or adapted to address this challenge.…”
Section: Building the Database And Infrastructure Of The Pcamentioning
confidence: 99%
“…Technology to detect and track retrograde signaling pathways from plastids to nuclei in response to, for example, singlet O 2 , protein folding stress, redox and metabolites. These retrograde pathways involve a range of small molecules and likely also protein signaling cascades ( Jiang and Dehesh, 2021 ; Muñoz and Munné-Bosch, 2020 ; Pesaresi and Kim, 2019 ). Non-invasive, high-resolution and high-sensitivity imaging technologies should be developed or adapted to address this challenge.…”
Section: Building the Database And Infrastructure Of The Pcamentioning
confidence: 99%
“…Since the various foliar metabolisms significantly rely on chloroplasts, it is indisputable that the ROS-driven chloroplast photodamage will negatively affect plant productivity, especially under fluctuating, severe, and long-lasting stress conditions. However, independent studies have revealed that chloroplast ROS can be beneficial for plants to adapt to distinct stress factors by triggering various signaling pathways from the stressed chloroplasts back to the nucleus, collectively referred to as operational retrograde signaling (ORS) [22,27,28]. For instance, the ROS-driven oxidation of proteins and an antioxidant compound (β-carotene) were found to be integral for activating ORS pathways in response to external stimuli, such as high light, cold, drought, and herbivores, thereby linking chloroplast photodamage to signaling [23,[29][30][31].…”
Section: Chloroplast Ros-mediated Operational Retrograde Signalingmentioning
confidence: 99%
“…In particular, the increased levels of chloroplast-localized HSP70 and ClpB3 chaperones seem to be essential for refolding the aggregated enzyme in the plastidial methylerythritol phosphate (MEP) pathway under oxidative stress conditions [11,18,55], suggesting that the MEP pathway tends to be deactivated in var2-9 and clp mutant plants. Since the MEP pathway is essential for maintaining photosynthesis and directly linked to the activation of retrograde signaling, a deactivation of the MEP pathway and/or accumu-lation of certain intermediates may trigger appropriate adaptive stress responses [27,56]. Indeed, one of the intermediates, methylerythritol cyclodiphosphate (MEcPP), induces a suite of nuclear genes encoding the core erUPR proteins [57], suggesting that chloroplast retrograde signals can modulate ER stress.…”
Section: Chloroplast Ftsh-dependent Proteostasis Functions In Photoprotectionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, drought causes plants to close their stomata to minimize water loss 25,26 , while heat causes the stomata to open to cool down their leaves via transpiration 21,27,28 . The stress signalling is mediated by a diverse ensemble of stress-specific sensors/receptors, networks of protein kinases/phosphatases, calcium channels/pumps, and transcription factors that can be localized to different organelles 29,30 . Stress signalling is further communicated and attenuated by hormones, other signalling molecules (e.g., reactive oxygen species) and protein modifications (s-nitrosylation, ubiquitination, myristoylation) 31,32 .…”
mentioning
confidence: 99%